Towards a selective cytotoxic agent for prostate cancer: interaction of zinc complexes of polyhydroxybenzaldehyde thiosemicarbazones with topoisomerase I - Tan, K.W.; Seng, H.L.; Lim, F.S.; Cheah, S.C.; Ng, C.H.; Koo, K.S.; Mustafa, Mohd Rais; Ng, S.W.; Maah, M.J. (2012)
Four thiosemicarbazones ligands,H3T(1),H3M(2),H3E(3) andH3P(4) have been prepared with good yield by refluxing 2,4-dihydroxybenzaldehyde with N(4)-substituted thiosemicarbazide in ethanol (H3T(1) = 2,4-dihydroxybenzaldehyde thiosemicarbazone;H3M(2) = 2,4-dihydroxybenzaldehyde 4-methylthiosemicarbazone; H3E(3) = 2,4-dihydroxybenzaldehyde 4-ethylthiosemicarbazone and H3P(4) = 2,4-dihydroxybenzaldehyde 4-phenylthiosemicarbazone). Reactions of these ligands with zinc acetates in the presence of 2,20-bipyridine lead to the formation of zinc(II) complexes of formulation Zn(bpy)L(5â8) (bpy = 2,20-bipyridine; L = doubly deprotonated thiosemicarbazones = HT(5); HM(6); HE(7) and HP(8)). These compounds were characterized and their cytotoxicity and topoisomerase I inhibition activities studied. X-ray diffraction study indicates that complex 8 is five coordinated and the coordination geometry around zinc(II) is trigonal bipyramidal distorted square based pyramid (TBDSBP). The doubly deprotonated thiosemicarbazone acts as a tridentate ONS-donor ligand while 2,2-bipyridne as the NN-donor ligand. Complexes 6, 7 and 8 are more cytotoxic towards PC3 (prostate cancer cell line) than RWPE-1 (prostate normal cell line). The cytotoxicity and topoisomerase I inhibition activities seem to be dependent on the N(4) substituent of the thiosemicarbazone moiety.